Kisan Call Centre Services to the Farming Community: An Analysis - S Kavitha; Nallusamy Anandaraja (Journal of Extension Education, 2018)
Kisan Call Centre (KCC) is one of the major initiatives taken up by the Ministry of Agriculture and Farmers Welfare, Government of India to provide timely agriculture and allied sector information to the farming community through landline or mobile connection. The service is provided through a toll-free number of 1800-180-1551. Considering the importance of KCC, the research study was conducted in Mahaboobnagar District of Telangana State in India with a sample size of 90 farmers to find out and analyze benefits obtained by the farming community through Kisan Call Centre Services. The results revealed that maximum number of the respondents expressed that KCC advisory was able to save cost of cultivation and in forecasting the pest and disease outbreak in a particular region. The study also showed that farming experience, source of irrigation, contact with extension agencies, participation in extension methods, perception towards mobile phones in farming and innovativeness showed positive and significant relationship with the benefits obtained by respondents.